Comparative experiment of steel bar corrosion at concrete construction joints - Huang, Guohua; Wu, Binzhong; Shen, Yin; Wang, Li; Li, Guoping (Frontiers in Materials, 2022)
Introduction: Construction joint is common and even inevitable in most of the reinforcement concrete structures. This study was to assess the effect of construction joints on chloride-induced corrosion of reinforcing steel in concrete. Methods: Test parameters included two environmental conditions (salt solution immersion condition and cyclic wet-dry condition), two forms of construction joint (direct wet joint and roughened wet joint) and four types of steel bar (mild steel bar, ferritic stainless-steel bar, austenitic-ferritic stainless-steel bar and epoxy-coated steel bar). The corrosion test of 90 specimens was carried out by electrochemical accelerated corrosion method. The weight loss of each steel bar and steel bar section in specimens was measured. An influence coefficient (k_j) of construction joint on local weigh loss of steel bars was defined. Results: Except for epoxy-coated steel bars, the most severe corrosion of experimental steel bars in concrete specimens all occurred at the joints, while the corrosion in non-joint sections of steel bars was relatively uniform and less. The weight loss rate of specimens has the range of 1.18% to 15.73% with an average value of 6.22%. The average k_j of mild steel bars, S11203 stainless steel bars, and S23043 stainless steel bars are 1.38, 1.92, and 1.97, respectively. The average k_j of specimens in immersion condition and cyclic wet-dry condition are 1.44 and 2.07. The corrosion of epoxy-coated steel bars mainly occurred at the damage locations of epoxy coating, not mainly at the joints. Conclusion: Chloride-induced corrosion of steel bars at construction joints was always more severe than at non-joints, especially in cyclic wet-dry environments, even for stainless-steel bar, but epoxy-coated steel bars were excluded.